An Intelligent Soft Sensor for Detecting Ammonia in a NanoFeCu Catalysed Sewage Treatment - Ngu, Joyce Chen Yen (Curtin University, 2023)
A novel intelligent soft sensor, PCA-DA-E-LSSVR, was developed for nanoFeCu catalysed ammonia removal process in wastewater treatment. It accurately predicted ammonia concentration using process variables. Comparative analysis showed superior predictive accuracy over commonly used models, such as ANN and SVR. The PCA-DA-E-LSSVR model, with coefficients of determination exceeding 0.7, outperformed in flow rate and nanoparticle regeneration parameter studies. This model also exhibited its efficacy in online ammonia concentration estimation and adaptability to online conditions.